Individualized estimates of intensity-modulated radiotherapy plans after breast conservation surgery for left-sided breast cancer - Yong Wang; Lingqin Ni; Shenpeng Ying; Yuanyuan Xu; Weijun Chen; Yanmei Liu (World Journal of Surgical Oncology, 2023)
Abstract Objectives The purpose of this study was to explore the influence of individual patient factors, such as volume of the planning target volume (PTV) (VPTV), cardiothoracic ratio (CTR), central lung distance (CLD), and maximal heart distance (MHD), on the design of treatment plans in terms of target dose coverage, integral dose, and dose to organs at risk (OAR) in early breast cancer. Methods Ninety-six patients were selected for this study. Radiation doses of 50 Gy and a simultaneous dose of 60 Gy in 25 fractions were administered to the whole breast and tumor bed, respectively. The intensity modulation plan (IMRT) of each patient uses both physical parameters and an equivalent uniform dose (EUD) to optimize the target function. Univariate and multivariate linear regression were used to analyze the relationship between predictive impact factors and OAR percent dose volume, conformity index (CI), and homogeneity index (HI). Results The average CI and HI values of the left breast cancer plan were 0.595 ± 0.071 (0.3–0.72) and 1.095 ± 0.023 (1.06–1.18), respectively. The CTR (B = 0.21, P = 0.045), VPTV (B = 0.63, P = 0.000), volume of the lung (Vlung) (B =  − 0.29, P = 0.005), and MHD (B = 0.22, P = 0.041) were identified as factors influencing the CI index of the left breast cancer intensity modulation plan. VPTV (B = 1.087, P = 0.022) was identified as the influencing factor of the HI index of the left breast cancer intensity modulation plan. volume of the heart (Vheart) (B =  − 0.43, P = 0.001) and CLD (B = 0.28, P = 0.008) were influencing factors of the volume of lung (Vlung20) of the lung. The prediction formulas for left-sided breast cancer are noted as follows: CI = 0.459 + 0.19CTR-0.16CLD, Vlung10 = 35.5–0.02Vheart; and Vlung20 = 21.48 + 2.8CLD-0.018Vheart. Conclusions CTR, CLD, and MHD can predict the rationality of the parameters of the left breast cancer IMRT. The calculation formula generated based on this information can help the physicist choose the optimal radiation field setting method and improve the quality of the treatment plan.